Comunidad de arañas (Arachnida, Araneae) del cultivo de alfalfa (Medicago sativa) en Buenos Aires, Argentina - Armendano, Andrea Viviana (2010)
Over the last decades there has been an increasing interest in the use of natural enemies to control pest insects, including spiders. We studied a spider community in Argentina by sampling every two weeks during 2004-2006 in one-hectare lots. Soil stratum spiders were collected using nets and pitfall traps. A total of 6229 specimens were collected (15 families and 50 species). Seven families were found in the herbal stratum, the most abundant were Thomisidae (n=2012, 32.30%), Araneidae (n=1516, 24.33%) and Oxyopidae (n=604, 9.70%). The soil had 14 families, mainly: Lycosidae (n=629, 10.10%) and Linyphiidae (n=427, 6.85%). Hunting spiders predominated: ambushers (32.99 %); stalkers (11.77%) and ground-runners (10.84%) were less common. The most abundant web building spiders were the orb weavers (27.56%). The diversity indexes were: H´=2.97, Dsp=0.11 and J=0.79, evidencing a moderately diverse spider community with predominance of Misumenops pallidus, Oxyopes salticus, Lycosa poliostoma and L. erythrognatha. The spiders were present throughout the phenological development of the crop with abundance peaks in spring and summer.